PERANAN BERBAGAI KOMPOSISI MEDIA TANAM ORGANIK TERHADAP PERTUMBUHAN BIBIT JABON MERAH (Anthocephalus macrophyllus) - Pala, Gloria Natalia; Seran, Wilhelmina; Pellondou, Mamie E. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
Jabon Merah (Anthocephalus macrophyllus) is one type of plant that has a strong growth resistance in its growth. Jabon Merah plants need nutrients in their growth. This study aims to determine the effect of providing chicken and cow manure on the growth of Jabon Merah plants. The research was conducted at the Fatukoa permanent nursery from December 2020 to March 2021. The method used was a Completely Randomized Design (CRD) method with one-factor testing, consisting of 7 treatments and 4 replications consisting of M0=100% Soil (Control) ( 2 kg); M1=75% soil + 25% chicken manure fertilizer (1.5 kg + 0.5 kg); M2= 50% soil + 50% chicken manure fertilizer (1 kg + 1 kg); M3=25% soil + 75% chicken manure fertilizer (0.5 kg + 1.5 kg); M4=75% soil + 25% cow manure (1.5 kg + 0.5 kg); M5 = 50% soil + 50% cow manure (1 kg + 1 kg); M6 = 25% soil + 75% cow manure (0.5 kg + 1.5 kg). Parameters observed and measured were increase in seedling height (cm), increase in stem diameter (cm), number of leaves (strands), shoot dry weight (gr), root dry weight (gr), seedling robustness (cm), root shoot ratio (gr), seed quality index and live percentage (%). The results showed that the application of chicken and cow manure showed no significant effect on all parameters, namely increase in seedling height (cm), increase in stem diameter (cm), number of leaves (strands), shoot dry weight (gr), root dry weight. (gr), seedling sturdiness (cm), root shoot ratio (gr), seedling quality index and live percentage (%).